Rational perception of reality and its relationship to ethical decision-making among female students of the kindergarten department (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the relationship between rational perception of reality and ethical decision-making among female students of the Kindergarten Department, and to achieve the objectives of the research, a random sample was selected and amounted to (482) female students from the Kindergarten Department in the College of Basic Education / Al-Mustansiriya University for the academic year (2020-2021), the researcher has built a scale of rational perception of reality consisting of three components, and also built an ethical decision-making scale consisting of six positions, each position has six alternatives, psychometric properties were extracted from the validity and reliability of the two scales, as the results indicate that there is a relationship between rational perception of reality and moral decision-making among students of the kindergarten department, but it is weak.